Dimensions of employee satisfaction with compensation: scale development and validation. (3rd September 2019) - Rahman, Subiya; Singh, Tripti
Employee satisfaction is deciphered in terms of contentment and is linked with the productivity of the organisation and thus is an important element for employee retention. The objective of the paper is to develop and validate a scale to measure the dimensions of employee satisfaction with compensation. A survey is conducted on a sample of 192 employees in public and private sector banks in India. The findings of the research demonstrate the validity and reliability of the scale and conclude five factors which are important to measure employee satisfaction with compensation viz., compensation structure/administration, pay level, organisational justice, pay raise, benefits and pay equity. The uniqueness of the scale lies in the fact that it measures satisfaction of employees with compensation and gives an impetus to organisation to further develop their compensation plan on the identified strategies.